Discourse Marker in the Tinker Bell Movie: Sociolinguistic Study - Puspa Putri Ruswina; Puspita Sari (Budapest International Research and Critics University, 2022)
The focus of this research is on the film Tinker Bell's discourse markers. A variety of discourse markers and their purposes are examined in this study, which can be seen in the Tinker Bell movie. In addition, the study explores the differences in speech patterns between male and female language speakers. The